Pengembangan Sistem Tender Online Dalam Pengadaan Barang Berbasis Web (Studi Kasus RS. Pelni Jakarta) - Firdaus Arsy Ramadhan; Fajar Pradana; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Tender or auction is one of the sales activities carried out in front of several people and is led by the auction official. Auction activities can be in the form of goods or services. PELNI Hospital is one of the hospitals in Jakarta that is not spared from procuring goods and services so that all needs in the hospital are met. In implementation, Hospital PELNI conducts auctions to procure goods and services to vendors. however, in the auction process there were problems including manual procurement of goods which made the transaction ineffective and the process of selecting potential vendor candidates who won the auction relatively took a long time because the process took 1 month. Based on these problems, a system was made to simplify the auction process in Pelni Jakarta Hospital. The system development process includes the requirements analysis, implementation, and testing stages. Stages of needs analysis to get 25 functional needs. The stages of implementation use the PHP programming language in the Laravel framework. Stages of testing include non-functional and functional testing. Functional testing includes unit tests that successfully carry out test paths based on 3 test cases, integration testing on the getRecommendedAttribute() method with penawaran() and get_formatted() yields a valid status and validation testing yields 100% valid from 31 test cases. Non-functional testing using usability with system results can be accepted by users with a score of 88 for the admin and a score of 84 for the vendor.